CADASIL presenting as late‐onset mania with anosognosia - Uppal, Manik (Clin Case Rep, 2019)
The diagnosis of cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) should be considered in patients with late‐onset personality change and mania. However, neuropsychological deficits precipitated by the disorder pose significant challenges to recognition and appropriate management of CADASIL in susceptible patients.